Development of Geography E-Modules Based on Project-Based Learning to Improve Senior High School Students' Learning Outcomes - Jumaylin Br Marpaung; Efendi Napitupulu; Sugiharto Sugiharto (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: The integration of digital media with student-centered learning approaches is crucial for enhancing education quality in the 21st century. However, geography instruction at SMA Negeri 1 Babalan still predominantly relies on textbooks and lacks interactive learning resources. This limitation reduces student engagement and leads to less-than-optimal learning outcomes.Aims: This study aimed to develop a valid, practical, and effective Geography E-Module based on the Project-Based Learning (PjBL) model for Grade X students. The module focused on the lithosphere topic and was designed to improve student learning outcomes.Methods: The research employed the ADDIE development model, consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection involved expert validations, teacher and student questionnaires, and pre-test and post-test assessments. Quantitative data were analyzed using descriptive statistics, paired t-tests, and N-Gain calculations.Result: The developed E-Module achieved high validation scores: 98% for content, 87% for media, and 86% for instructional design. The practicality rating reached 94.45%. A statistically significant improvement was found in the experimental group's learning outcomes compared to the control group (t = 2.37 > t-table = 1.670). The N-Gain score of 0.41 indicated a moderate level of effectiveness in enhancing student performance.Conclusion: The Project-Based Learning-based Geography E-Module is valid, practical, and effective in supporting student-centered learning. It successfully enhances student engagement and learning outcomes, making it a valuable instructional resource for senior high school geography education.